Fuzzy Language Processing in Translation of Literature: A Case Study of Dr. Zha 's Diary of Fighting the COVID-19 - Yang, Aijun (Theory and practice in language studies, 2021)
Aesthetics is a subject focusing on studying the nature and significance of beauty (including beauty in language, art, literature, etc.). Moreover, the development of aesthetics, within the broader context of literary systems, is of significant importance. Chinese Literature (which in essence differs from that of English Literature) expresses beauty using its unique ways, especially with the employment of fuzzy language (also known as "vague language"). By including a certain degree of "fuzziness", Chinese Literature grants readers room fir imagination. However, the process of translating Chinese fuzzy language into other languages is not an easy feat to accomplish. Such translations can, to a large extent, seriously affect the original meaning of the text. To explore proper ways of "fuzzy language" translation, this paper ventures to analyze the processing methods used in the translated work "Dr. Zha's Diary of Fighting the COVID-19". Categorizing vague language into three perspectives, namely, semantic vagueness, cultural vagueness and rhetorical vagueness, the paper analyzes the way to tackle fuzzy language with 16 detailed cases. Based on the case analyses, the paper proposes that the proper translation of fuzzy language in literature will be more conducive for readers to appreciate the works and helps to improve the translation quality. By exploring the ways of processing fuzzy language, this paper hopes to bring some suggestions and inspiration to other researchers. Index Terms--fuzzy language, Dr. Zha's Diary of Fighting the COVID-19, translation strategy